Self-Compassion Based on Gender and Student Academic Achievement - Setiani, Ismarini Bekti; Titi, Dwitias (Jurnal Kajian Bimbingan dan Konseling, 2023)
This study aims to determine the effect of gender on the level of students’ self-compassion and determine the effect of students’ level of self-compassion on their academic achievement. This study uses a quantitative approach, with the type of ex-post facto research and ordinal regression analysis. The data were collected using the Self-Compassion Scale (SWD) with alternative answers from one to five of scale. The sample in this study was students at Universitas Negeri Yogyakarta. Our analysis results showed no significant effect of gender on the students’ level of self-compassion and no significant effect of students’ level of self-compassion on their academic achievement.